The Protective Effects of a Combination of an Arginine Silicate Complex and Magnesium Biotinate Against UV-Induced Skin Damage in Rats - Cicek, Demet; Demir, Betul; Orhan, Cemal; Tuzcu, Mehmet; Ozercan, Ibrahim Hanifi; Sahin, Nurhan; Komorowski, James; Ojalvo, Sara Perez; Sylla, Sarah; Sahin, Kazim (Frontiers in Pharmacology, 2021)
The purpose of this study was to observe the effects of a novel combination of inositol-stabilized arginine silicate complex (ASI) and magnesium biotinate (MgB) on the prevention of skin damage after UVB exposure in rats. Forty-nine Sprague-Dawley rats were randomized into one of the following groups: (1) NC, normal control, (2) SC, shaved control, (3) UVB (exposed to UVB radiation), (4) ASI+MgB-L (Low Dose), (5) ASI+MgB-H (High Dose), (6) ASI+MgB-L+MgB cream, (7) ASI+MgB-H+MgB cream. The results showed that ASI+MgB treatment alleviated the macroscopic and histopathological damages in the skin of rats caused by UVB exposure. Skin elasticity evaluation showed a similar trend. ASI+MgB increased serum Mg, Fe, Zn, Cu, Si, biotin, and arginine concentrations and skin hydroxyproline and biotinidase levels while decreasing skin elastase activity (P < 0.05) and malondialdehyde (MDA) concentration (P < 0.001). Moreover, ASI+MgB treatment increased skin levels of biotin-dependent carboxylases (ACC1, ACC2, PC, PCC, MCC) and decreased mammalian target of rapamycin (mTOR) pathways and matrix metalloproteinase protein levels by the regulation of the activator protein 1 (AP-1), and mitogen activated protein kinases (MAPKs) signaling pathways. In addition, ASI+MgB caused lower levels of inflammatory factors, including TNF-α, NFκB, IL-6, IL-8, and COX-2 in the skin samples (P < 0.05). The levels of Bax and caspase-3 were increased, while anti-apoptotic protein Bcl-2 was decreased by UVB exposure, which was reversed by ASI+MgB treatment. These results show that treatment with ASI and MgB protects against skin damage by improving skin appearance, elasticity, inflammation, apoptosis, and overall health.